Analyzing the Effectiveness of Internal Control Systems in Managing Pharmaceutical Inventories at Advent Hospital Medan, Indonesia - Sormin, Ropinna Nadia; Manurung, Amran; Siringoringo, Magdalena Judika Br (Golden Ratio of Data in Summary, 2025)
This study aims to analyze the implementation of the internal control system in managing pharmaceutical inventory at Advent Hospital Medan. Medication inventory plays a crucial role in supporting patient services, both outpatient and inpatient. Internal control is essential to ensure drug availability, prevent overstocking or stockouts, and mitigate risks of damage and expiration. This research uses a descriptive qualitative method, employing interviews and observations within the pharmacy department. The findings indicate that Advent Hospital Medan has implemented internal controls through inventory recording, stock monitoring, and task segregation. However, challenges such as overstocking and the risk of expired medications remain. Therefore, regular supervision and evaluation must be strengthened to optimize inventory management. This study is expected to serve as an input for hospital management and a reference for future research.